Determination of the Gastrointestinal Passage Rate Using Dexa Technology and Barium Sulfate As a Marker in Japanese Quails - Raimundo, E. K.M. [UNESP]; Carvalho, L. C. [UNESP]; Sousa, M. G.B.L. [UNESP]; Veras, A. G. [UNESP]; Lima, M. B. [UNESP]; Amoroso, L. [UNESP]; Artoni, S. M.B. [UNESP]; Silva, Edney P. [UNESP] (FapUNIFESP (SciELO), 2023)
The objective of this study was to characterize the dynamics of food passage in the gastrointestinal tract (GIT) of Japanese quail. A randomized design was used with four treatments and four experimental units with one bird each, nine of which were measured in time. The ingredients used were albumin, starch, cellulose, and soybean oil. Suspensions containing barium sulfate and saline were prepared, except for soybean oil. For each bird, 2.5 mL of the suspension was administered directly to the crop. Dual-energy absorptiometry (DEXA) was used to quantify the passage of food. The birds were sedated and maintained under inhalation anesthesia during the scan. Measurements were taken at intervals of 0.5, 1, 2, 4, 6, 8, 10, 12, and 24 h. The variables identified were passage time, first quality, and the average time of each variable. Based on these results, the ingredients may show differences in dynamic passing on the Japanese quail GIT. The duration of the first attempt was 32 min, ranging from 21 to 44 min. The average time value of food choice was close to 10.8 h and varied according to the ingredient from 8.45–12.16 h. Among the variables, soybean oil presented values that denote a fast passage in the GIT, while albumin presented values that denote a slower passage. The dynamics of food passage in the GIT of Japanese quails varies according to the chemical composition of the ingredients.
Keywords: First appearance time; Japanese quail; mean retention time; rate of passage; transit time